Validation and Extrapolation of a Multimodal Infection Prevention and Control Intervention on Carbapenem-Resistant Klebsiella pneumoniae in an Epidemic Region: A Historical Control Quasi-Experimental Study - Dai, Yunqi; Meng, Tianjiao; Wang, Xiaoli; Tang, Bin; Wang, Feng; Du, Ying; Qiu, Yuzhen; Liu, Jialin; Tan, Ruoming; Qu, Hongping (Frontiers in Medicine, 2021)
Objective: To verify the effects of comprehensive infection prevention and control (IPC) interventions for the prevention of the cross-transmission of carbapenem-resistant Klebsiella pneumoniae (CRKP) within intensive care units (ICUs) in an epidemic region. Methods: A historical control, quasi-experimental design was performed. The study was conducted between January 2017 and December 2019, following the implementation of a multimodal IPC bundle. The baseline period was established from January 2013 to June 2013, when only basic IPC measures were applied. Results: A total of 748 patients were enrolled during the entire study. The incidence of ICU-acquired CRKP colonization/infection was 1.16 per 1000 patient-days during the intervention period, compared with 10.19 per 1000 patient-days during the baseline period (p = 0.002). The slope of the monthly incidence of CRKP at admission showed an increasing trend (p = 0.03). The incidence of ICU-acquired catheter-related bloodstream infections caused by CRKP decreased from 2.54 to 0.96 per 1000 central-line-days (p = 0.08). Compliance with contact precautions and terminal room disinfection improved during the intervention period. All environmental surface culture samples acquired after terminal room disinfection were negative for CRKP. Conclusion: Our findings suggest that in epidemic settings, multimodal IPC intervention strategies and consistent monitoring of compliance, may limit the spread of CRKP in ICUs.